ANALISIS PENGALAMAN PENGGUNA PADA APLIKASI TOKOPEDIA DENGAN MENGGUNAKAN METODE USER EXPERIENCE QUESTIONNAIRE (UEQ) - Muhammad Faris; Suci Ratnawat (JURNAL PERANGKAT LUNAK, 2023)
Technology is developing rapidly, including buying and selling activities, which are increasingly influenced by e-commerce applications. Tokopedia is one of the largest e-commerce companies in Indonesia and has an important role in online buying and selling activities between sellers and buyers. However, in an increasingly competitive environment, the success of retaining and attracting users relies heavily on a positive user experience when using the app. A positive user experience is very important for maintaining and attracting users on e-commerce platforms. This research uses the User Experience Questionnaire (UEQ) method to analyze the user experience on the Tokopedia application. In this study, 30 UIN Jakarta information system students class of 2021 who are Tokopedia users became respondents. The evaluation results showed an overall positive impression of the Tokopedia application. However, the stimulation element scored below average, indicating the need for efforts to improve user experience in this aspect. In the face of competitive rivalry, appropriate steps can be taken to improve and enrich the user experience in terms of stimulation of the Tokopedia app. The importance of positive user experience in e-commerce apps is a crucial factor for retaining users and attracting more users in the future.